New Methods of Damage and Failure Analysis of Structural Parts - The Conference 'New Methods of Damage and Failure Analysis of Structural Parts' (September 10-14, 2018, Technical University of Ostrava-VSB, Czech) - Strnadel Bohumír (Trans Tech Publications, 2019)
The book covers a broad range of topics related to damage, failure, wear structural materials and parts and some technological aspects that provide the necessary strength properties of these materials. The collection contains the results of research and analysis of the fracture behavior of the materials that are subject to fatigue, stress corrosion cracking and extreme plastic deformation including analysis of the failures. Several papers focus on the microstructure of materials and prediction of their lifespan based on the knowledge of damage processes. The articles present various aspects of experimental, theoretical and computational investigations with an emphasis on the direct applications in engineering. The book was comprised of the papers presented at the conference "New Methods of Damage and Failure Analysis of Structural Parts" (September 10-14, 2018, Technical University of Ostrava-VSB, Czech).